2006
DOI: 10.1084/jem.20052222
|View full text |Cite
|
Sign up to set email alerts
|

T-bet negatively regulates autoimmune myocarditis by suppressing local production of interleukin 17

Abstract: Experimental autoimmune myocarditis (EAM) appears after infectious heart disease, the most common cause of dilated cardiomyopathy in humans. Here we report that mice lacking T-bet, a T-box transcription factor required for T helper (Th)1 cell differentiation and interferon (IFN)-γ production, develop severe autoimmune heart disease compared to T-bet −/− control mice. Experiments in T-bet −/− IL-4−/− and T-bet −/− IL-4Rα−/− mice, as well as transfer of heart-specific Th1 and Th2 cell lines, showed that autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
229
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(256 citation statements)
references
References 64 publications
20
229
1
1
Order By: Relevance
“…This is in accordance with a recent study in which both T-bet ϩ/ϩ and T-bet Ϫ/Ϫ pathogenic CD4 ϩ T cell lines produced elevated levels of IFN-␥ or IL-4, respectively, but also secreted significant and comparable amounts of IL-17 (26). Interestingly, one model of autoimmunity, experimental autoimmune myocarditis (EAM), has been found to have increased disease severity in T-bet-deficient mice (26). Increased numbers of Th17 cells and decreased numbers of IFN-␥ ϩ CD8 ϩ T cells in the hearts of T-bet-deficient mice led the authors to conclude that T-bet is a negative regulator of EAM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in accordance with a recent study in which both T-bet ϩ/ϩ and T-bet Ϫ/Ϫ pathogenic CD4 ϩ T cell lines produced elevated levels of IFN-␥ or IL-4, respectively, but also secreted significant and comparable amounts of IL-17 (26). Interestingly, one model of autoimmunity, experimental autoimmune myocarditis (EAM), has been found to have increased disease severity in T-bet-deficient mice (26). Increased numbers of Th17 cells and decreased numbers of IFN-␥ ϩ CD8 ϩ T cells in the hearts of T-bet-deficient mice led the authors to conclude that T-bet is a negative regulator of EAM.…”
Section: Discussionsupporting
confidence: 93%
“…However, we found Th17 cells differentiated in the CNS of EAE-affected mice in the presence of IFN-␥-producing Th1 cells. This is in accordance with a recent study in which both T-bet ϩ/ϩ and T-bet Ϫ/Ϫ pathogenic CD4 ϩ T cell lines produced elevated levels of IFN-␥ or IL-4, respectively, but also secreted significant and comparable amounts of IL-17 (26). Interestingly, one model of autoimmunity, experimental autoimmune myocarditis (EAM), has been found to have increased disease severity in T-bet-deficient mice (26).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IL-17 production was also shown to be enhanced in IFN-g À/À mice infected with BCG, whereas addition of recombinant IFN-g inhibited in vitro activation of Th17 cells by DC infected with BCG [100]. In an experimental autoimmune myocarditis model, T-bet-mediated IFN-g production by CD8 1 T cells was found to regulate IL-17 production and thereby control the severity of myocarditis [101]. IFN-g may also play a role in controlling pathogenic T cells in autoimmunity by inducing peripheral conversion of CD4 1 CD25 À T cells into CD4 1 FoxP3 1 Treg cells [102].…”
Section: Regulation Of Il-17-secreting T Cellsmentioning
confidence: 94%
“…Huber and others discovered that male mice who mostly had a Th1 cell-mediated immune response were more susceptible to the CVB3 virus than female mice who had a Th2-mediated immune response [3]. Rangachari et al reported that Th17 cells and its cytokine, IL-17, increased the severity of viral myocarditis and autoimmune myocarditis [4]. Treg cells could inhibit the expression of inflammatory cytokines and attenuate the severity of viral myocarditis [5].…”
Section: Introductionmentioning
confidence: 99%